Tiaogan Bushen Xiaoji Formula Enhances the Sensitivity of Estrogen Receptor- Positive Breast Cancer to Tamoxifen by Inhibiting the TGF-β/SMAD Pathway - Lu J; Li Z; Liu X; Xu B; Zhang W (Cancer Management and Research, 2024)
Jiafeng Lu,1,* Zhaoyan Li,2,* Xingjing Liu,2 Bin Xu,1 Weiyu Zhang2 1Department of Pharmacy, Ruijin Hospital, Shanghai Jiaotong University, Shanghai, People’s Republic of China; 2Department of Traditional Chinese Medicine, Ruijin Hospital, Shanghai Jiaotong University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weiyu Zhang, Department of Traditional Chinese Medicine, Ruijin Hospital, Shanghai Jiaotong University, Shanghai, 200025, People’s Republic of China, Tel +86-021-67888394 ; Tel +86-13818103558, Email zhangweiyu33@163.com Bin Xu, Department of Pharmacy, Ruijin Hospital, Shanghai Jiaotong University, Shanghai, 200025, People’s Republic of China, Tel +86-021-67888176 ; Tel +86-18917762607, Email xb40291@rjh.com.cnBackground: The resistance to endocrine therapy can lead to recurrence and metastasis of breast cancer (BC), affecting the survival period. Tiaogan Bushen Xiaoji (TGBSXJ) Formula, a traditional Chinese medicine (TCM) decoction, has been widely used in the treatment of estrogen receptor-positive (ER+) BC. However, the underlying mechanism of TGBSXJ Formula in ER+BC treatment has not been totally elucidated.Methods: Network pharmacology (NP) and RNA sequencing were used to predict the candidate ingredients and explore the potential targets of TGBSXJ Formula. Then, the results of NP and RNA sequencing were investigated by in vitro experiments.Results: Active ingredients of TGBSXJ Formula mainly included Mangiferin, Rutin, Anemarrhena asphodeloides saponin BII, Ganoderic acid A and Acacetin, etc. A protein-protein interaction (PPI) network was created based on the active ingredients of TGBSXJ Formula and target genes of ER+ BC, in which TGF-β, MMP2 and SMAD3 were defined as the hub genes. In vitro experiments showed that TGBSXJ Formula significantly inhibited the viability, colony ability and migration of ER+ BC cells, and significantly increased the sensitivity to TAM. Western blot analysis showed that TGBSXJ Formula significantly downregulated TGF-β, E-cadherin, MMP2, MMP9, N-cadherin, p-Smad2 and p-Smad3 in ER+ BC cells.Conclusion: TGBSXJ Formula increases the sensitivity of ER+ BC cells to TAM by inhibiting the TGF-β/Smad signaling pathway.Keywords: estrogen receptor-positive breast cancer, network pharmacology, traditional Chinese medicine, endocrine resistance